Regulation of Tmem30b-mediated apical membrane homeostasis in auditory outer hair cells is critical for hearing - Miao Chang; Guodong Hong; Shan Gao; Cheng Cheng; Jia Yuan; Yu Xiao; Ruifeng Qiao; Jing Ke; Xinhao Wu; Tiancheng Zhang; Siwei Guo; Runze Jiang; et al. (Proceedings of the National Academy of Sciences, 2026)
Mechanotransduction within the cochlea depends on the precise architecture of hair bundles, yet our comprehension of the mechanisms that govern the formation and maintenance of the sound-receptive structure is still limited. Here, we identify Tmem30b, a phospholipid-flippase chaperone, as a critical regulator expressed in outer hair cells (OHCs). Although initially localized to the nuclear membrane at P5, Tmem30b translocates to and stabilizes within the stereocilia and the underlying cuticular plate during maturation. The Tmem30b −/− mice exhibit an early-onset hearing loss with preserved vestibular and retinal functions. Notably, the disorganization of OHC stereocilia in mutants initiates at P7, coinciding with the initial presence of Tmem30b in stereocilia. Mechanistically, Tmem30b partners with Atp8b1 to regulate phospholipid asymmetry; disruption of this complex destabilizes OHC bundles. Crucially, AAV-mediated delivery of Tmem30b t o hair cells alleviates stereocilia defects in both Tmem30b −/− and Atp8b1 −/− mice. Furthermore, hair cell specific overexpression of Tmem30b protects mice from noise-induced and aminoglycoside-induced hearing loss. In summary, our findings establish Tmem30b as a pivotal organizer of OHC hair bundles and highlight Tmem30b–Atp8b1–mediated lipid regulation as a therapeutic target for hearing loss.